2006
DOI: 10.2307/j.ctv6cfqtv
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Television Today

Abstract: The artwork on the cover of this book is not open access and falls under traditional copyright provisions; it cannot be reproduced in any way without written permission of the artists and their agents. The cover can be displayed as a complete cover image for the purposes of publicizing this work, but the artwork cannot be extracted from the context of the cover of this specific work without breaching the artist's copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…As we unravel this tightly woven text of cultural contradiction, we arrive at the core of a man who offers us insight and his version of truth. Cherry is an important aspect of the Canadian image; through him we see what is missing, [and] the fact that Don Cherry, a hockey commentator, is the best-known public face of the national broadcaster is demonstrative of how little interest Canadian television mandarins have in multiculturalism (Beaty & Sullivan, 2006).…”
Section: Hockey As Cultural Institutionmentioning
confidence: 99%
“…As we unravel this tightly woven text of cultural contradiction, we arrive at the core of a man who offers us insight and his version of truth. Cherry is an important aspect of the Canadian image; through him we see what is missing, [and] the fact that Don Cherry, a hockey commentator, is the best-known public face of the national broadcaster is demonstrative of how little interest Canadian television mandarins have in multiculturalism (Beaty & Sullivan, 2006).…”
Section: Hockey As Cultural Institutionmentioning
confidence: 99%
“…Previous research by Beaty and Sullivan (2006, 83) has suggested that rather than a celebration of any form of national symbolic culture, the Canadian adaptation of Pop Idol, Canadian Idol is “numbingly formulaic,” reiterating that the homogenizing feature of an international format, its delocalization and shallow localization, allows it to travel from nation to nation, and a flat version of Canada is presented. This is one of the few articles suggesting that the inclusion of Canadian artists, media events that “embed .…”
Section: Sytycdc and Commercial Nationalist Discoursesmentioning
confidence: 99%
“…The derivative nature of the Canadian version begets immediate comparison. Defensive comparison is not new to Canadian television and culture—many expressions of Canadian cultural nationalism, in content and policy, have historically developed in response to the power of the States (Attallah 1996; Beaty and Sullivan 2006). This program functions as a contemporary imprint of a long-standing argument and conundrum in the development of Canadian national identity (Mackey 2002).…”
Section: Sytycdc and Commercial Nationalist Discoursesmentioning
confidence: 99%
See 2 more Smart Citations